Biology and ecology of fishes - Diana, James S.; Hook, Tomas O. (John Wiley & Sons, Inc., 2023)
Studies of fishes have historically taken two divergent directions. The first, a more academic approach emerging from universities, has dealt with systematics, anatomy, physiology, and theoretical ecology. The second, a more practical approach emanating from natural resource organizations, has emphasized fishery biology, population ecology, and fishery management. In recent years, these distinct trends have become more mixed, as teachers and students have realized the importance of both lines of inquiry and have crossed this boundary. However, this dual purpose has been less common in the published literature, particularly textbooks, in the field. This book attempts to break that mold and to consider both biological and management needs in the field of fish ecology"-- Provided by publisher.